2022
DOI: 10.4266/acc.2022.00129
|View full text |Cite
|
Sign up to set email alerts
|

The effect of socioeconomic status, insurance status, and insurance coverage benefits on mortality in critically ill patients admitted to the intensive care unit

Abstract: Socioeconomic status is well known to be related to mortality [1] and is an important health issue in the management of the intensive care unit (ICU) in the United States and Europe [2]. Previous research also shows that the absence of health insurance is associated with a higher mortality rate among patients admitted to the ICU but unadjusted for the severity of illness and data from a single center [3]. Many observational studies have similarly suggested that a lack of insurance is associated with a higher m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In 2019, a systemic review of 10 studies found patients with socioeconomic disadvantage had higher mortality across critical illness continuum; the authors advocated for inclusion of socioeconomic demographics in future critical care studies [51]. In a recent longitudinal study, Jain et al [52 ▪ ] evaluated the association of individual-level socioeconomic disadvantage, represented by dual-eligibility for Medicaid and Medicare, with the three outcomes of the post-ICU syndrome: physical function (operationalized as disability in ADLs), cognitive function, and mental health symptoms [53]. Socioeconomic disadvantage was associated with a 28% increase in disability and 9.8-fold greater odds of developing probable dementia in the year after critical illness.…”
Section: Socioeconomic Disadvantagementioning
confidence: 99%
“…In 2019, a systemic review of 10 studies found patients with socioeconomic disadvantage had higher mortality across critical illness continuum; the authors advocated for inclusion of socioeconomic demographics in future critical care studies [51]. In a recent longitudinal study, Jain et al [52 ▪ ] evaluated the association of individual-level socioeconomic disadvantage, represented by dual-eligibility for Medicaid and Medicare, with the three outcomes of the post-ICU syndrome: physical function (operationalized as disability in ADLs), cognitive function, and mental health symptoms [53]. Socioeconomic disadvantage was associated with a 28% increase in disability and 9.8-fold greater odds of developing probable dementia in the year after critical illness.…”
Section: Socioeconomic Disadvantagementioning
confidence: 99%